PKM Pendalaman Iman Katolik Peserta Didik Sekolah Dasar Melalui Pendekatan Contextual Teaching and Learning - Aurelius Fredimento (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
This Community Service Program (PKM) aims to enhance the quality of Catholic faith formation among students at Pelibaler Elementary School by implementing the Contextual Teaching and Learning (CTL) method, supported by audiovisual media. The program is grounded in the need for a more creative, relevant, and contextual approach to faith education for children who live in an era marked by rapid digital information flows. The CTL approach was chosen because it positions learners as active participants capable of linking religious teachings with their everyday life experiences, thereby fostering a learning process that engages not only the cognitive domain but also the affective and spiritual dimensions. The use of audiovisual media further supports students in understanding faith values in a more concrete, engaging, and comprehensible manner. The implementation included several stages: contextual delivery of faith materials, reflective experience-based activities, group discussions, and a value internalization phase that included an evening of silence and contemplation, followed by a concluding Eucharistic celebration. Evaluation results indicate that the CTL method supported by audiovisual media significantly enhances students’ understanding, engagement, and depth of spiritual reflection. Participant satisfaction data show that the majority fall into the satisfied and very satisfied categories, demonstrating the effectiveness of this method and its suitability for the cognitive and spiritual development of elementary school children. Furthermore, the program highlights that structured faith experiences that address affective dimensions play an essential role in holistic faith formation. As a follow-up, the school is recommended to develop a sustained CTL-based audiovisual module, provide further training for religious teachers and facilitators, and conduct regular faith formation activities. Thus, this PKM initiative not only yields short-term impact but also serves as a foundation for more systematic, creative, and contextual faith development efforts in the future.